Predictive model of mentalization based on attachment styles with the mediating role of ego empowerment in students - Zahra Bahrololoum; Hoda Lajevardi (مجله علوم روانشناختی, 2025)
Background: Attachment styles and mentalizing are among the psychological factors that are related to emotion regulation skills, the use of mentalizing ability is related to the ability of the ego in people. Therefore, investigating the path of mentalizing evolution through attachment styles to ego empowerment is a basic necessity. Aims: The purpose of this study was to predict mentalizing based on attachment styles with the mediating role of ego empowerment in students. Methods: The research method is descriptive-correlational, which was done using structural equation modeling. The study population includes all students of the Faculty of Humanities of the Islamic Azad University of Qom Branch in 2023-2024. The sample consisted of 335 students of Islamic Azad University, Qom Branch, who were selected by convenience sampling method and answered the Reflective Performance Questionnaire (Fonagy et al., 2016), Adult Attachment Styles Questionnaire (Collins & Reed, 1990), and Ego Empowerment Scale (Markstrom et al., 1997). To analyze the data, structural equation modeling was used using SPSS version 19 and Amos software version 24. Results: The results of structural equation modeling showed that secure attachment style, avoidant attachment, ambivalent attachment, and ego empowerment had a direct and significant causal effect on confidence and uncertainty (P< 0.05). Also, ambivalent attachment style, secure attachment style, and avoidant attachment style had a direct and significant causal effect on ego empowerment (P< 0.05). The results also showed that 60% of the variance of ego empowerment is explained by attachment styles, 23% of the variance of confidence, and 46% of the variance of uncertainty is explained by attachment styles and ego empowerment. Conclusion: Based on the findings of the research, it can be concluded that secure attachment style, avoidant attachment, ambivalent attachment, and ego empowerment as factors affecting mentalizing can lead us to a deeper understanding of mentalizing, and by teaching students the formation of different attachment styles and ego structure, mentalizing can be strengthened in them.